THE ANALYSIS OF INFLUENCING FACTORS OF OFFERING RICE PRICE IN SERDANG BEDAGAI REGENCY - Esty Surya Ramadhani; Muhammad Yusuf (Universitas Negeri Medan, 2020)
The world's back is concerned with food security issues for the community, pecially from the dimensions of availability, access to food and food price stability. Countries should be able to increase production in order to provide food rice sufficiency and sustainable, but on the other hand there are many factors that affect the level of availability of rice in the community. This study aimed to analyze the influence of the harvested area, the price of rice, the price of bread, and rainfall to supply rice in Serdang Bedagai. In measuring and analyzing regression analysis model was used Ordinary Least Square (OLS) with a data processor Eviews 6.0. By using secunder data from BPS Serdang Bedagai during the period 2011 - 2015. The results showed that the independent variables used to explain the variables rice deals (PB) indicate the direction of influence in accordance with the hypothesis. Area harvested and the price of rice positive and significant impact on rice deals (PB) while the price of bread and rainfall positive effect but not significant to supply rice (PB) in Serdang Bedagai Regency, North Sumatra Province.